Return to Play and Career Length After Anterior Cruciate Ligament Reconstruction Among Canadian Professional Football Players. Issue 7 (June 2020) - Longstaffe, Robert; Leiter, Jeff; Gurney-Dunlop, Tanner; McCormack, Robert; MacDonald, Peter
Background: For many athletes, a tear of the anterior cruciate ligament (ACL) represents a significant injury that requires a prolonged period away from the sport with substantial rehabilitation. Hypothesis: There will be no difference in return to play (RTP) and career length after hamstring tendon (HT) ACL reconstruction in a group of Canadian Football League professional players as compared with what has been already been reported in the literature among professional football players. Study Design: Case-control study; Level of evidence, 3. Methods: Data on athletes who sustained an ACL injury were collected by team physicians and head athletic trainers from 2002 to 2017 from 2 Canadian Football League teams. Patient details included age at the time of injury, initial injury date, position, practice versus game injury, and primary versus rerupture with injury-specific data, such as affected limb, concomitant injuries, graft choice, and procedure performed. RTP rates and career length data were collected through publically available internet sources. Comparisons between the non-RTP and RTP groups were made with independent-sample t tests. Binomial logistic regression was performed to determine variables (ie, games preinjury, graft type, meniscal injury, collateral ligament injury) that contributed to players not being able to RTP. Results: A total of 44 ACL reconstructions were performed over the study period (HT, n = 32 [72.7%]; bone–patellar tendon–bone [BPTB], n = 8 [18.2%]; allograft, n = 4 [9.1%]). Overall, 69.8% (n = 30) were able to RTP in at least 1 game, while 30.2% (n = 13) did not return. Mean time to return was 316.1 days (range, 220-427 days), or 10.4 months. For those players who did RTP, mean career length after ACL reconstruction was 2.8 seasons, or 34.4 games. The majority (56.8%) of injuries occurred early in the season. Breakdown by graft type demonstrated RTP rates among HT, BPTB, and allograft of 64.5% (n = 20), 87.5% (n = 7), and 75% (n = 3), respectively. Career length among HT, BPTB, and allograft was 2.9, 2.4, and 3 seasons. Logistic regression analysis found only concomitant medial collateral ligament (MCL) injuries to be a negative predictor for RTP. Meniscal injuries were associated with a decreased RTP rate and career length, but this was not statistically significant. Conclusion: The RTP rates after ACL reconstruction in this study are similar to those reported in National Football League players. A concomitant injury to the MCL injury was a negative predictor of RTP. Meniscal injuries demonstrated a trend for decreased RTP rate and career length, but this was not a significant predictor. A large portion of injuries occur early in the season, and further study should be done to examine potential preventative strategies to reduce ACL injuries.